Apparent motion perception in lower limb amputees with phantom sensations: "obstacle shunning" and "obstacle tolerance". (July 2018) - Saetta, Gianluca; Grond, Ilva; Brugger, Peter; Lenggenhager, Bigna; Tsay, Anthony J.; Giummarra, Melita J.
Abstract: Phantom limbs are the phenomenal persistence of postural and sensorimotor features of an amputated limb. Although immaterial, their characteristics can be modulated by the presence of physical matter. For instance, the phantom may disappear when its phenomenal space is invaded by objects ("obstacle shunning"). Alternatively, "obstacle tolerance" occurs when the phantom is not limited by the law of impenetrability and co-exists with physical objects. Here we examined the link between this under-investigated aspect of phantom limbs and apparent motion perception. The illusion of apparent motion of human limbs involves the perception that a limb moves through or around an object, depending on the stimulus onset asynchrony (SOA) for the two images. Participants included 12 unilateral lower limb amputees matched for obstacle shunning (n = 6) and obstacle tolerance (n = 6) experiences, and 14 non-amputees. Using multilevel linear models, we replicated robust biases for short perceived trajectories for short SOA (moving through the object), and long trajectories (circumventing the object) for long SOAs in both groups. Importantly, however, amputees with obstacle shunning perceived leg stimuli to predominantly move through the object, whereas amputees with obstacle tolerance perceived leg stimuli to predominantly move around the object. That is, in people who experience obstacle shunning, apparent motion perception of lower limbs was not constrained to the laws of impenetrability (as the phantom disappears when invaded by objects), and legs can therefore move through physical objects. Amputees who experience obstacle tolerance, however, had stronger solidity constraints for lower limb apparent motion, perhaps because they must avoid co-location of the phantom with physical objects. Phantom limb experience does, therefore, appear to be modulated by intuitive physics, but not in the same way for everyone. This may have important implications for limb experience post-amputation (e.g., improving prosthesis embodiment when limb representation is constrained by the same limits as an intact limb).